Hubungan antara tinggi dan panjang mandibula di radiograf panoramik dengan kadar kalsium pada pasien lanjut usia - Ichda Nabiela Amiria Asykarie; Lusi Epsilawati; Ria Noerianingsih Firman; Farina Pramanik (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: The aim of this research is to know about the correlation between calcium levels and mandibular height and length in elderly patients from panoramic radiographs. Materials and Methods: This study was a cross-sectional observational study, using 15 panoramic radiographs of patients aged 60-80 years, where each subject is taken calcium levels. Radiographs were analyzed to measure the length of the mandibular body and the height of the mandibular ramus. ImageJ software is used as a measuring tool, and the results are then correlated with the Pearson correlation test analysis. Results: This study obtained the average result for mandibular length was ± 10 cm and for mandibular height was ± 7 cm, while the calcium value showed an average value of ± 8.7-10 mg/dl. Pearson correlation test showed no significant relationship between mandibular length and height and calcium levels in the elderly. Conclusion: The conclusion drawn was that there is no significant relationship between mandibular height and length on calcium levels in the elderly as assessed by panoramic radiographs.